Identity-based cloud storage integrity checking from lattices - Miaomiao TIAN; Chuang GAO; Jie CHEN (Tongxin xuebao)
With the rapid development of cloud storage,more and more users are storing their data in the cloud.To verify whether the users’ data stored in the cloud is corrupted,one effective method is to adopt cloud storage integrity checking schemes.An identity-based cloud storage integrity checking scheme was proposed on the small integer solution problem over ideal lattices,and it was proven to be secure against the adaptive identity attacks of clouds in the random oracle model.To validate the efficiency of the scheme,extensive experiments were conducted to make performance-comparisons between the scheme and the existing two identity-based cloud storage integrity checking schemes.The experimental results show that the online tag-generation time and the proof-verification time of the scheme are respectively reduced by 88.32%～93.74% and 98.81%～99.73%.